2012
DOI: 10.1017/s1751731111002333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of staged ovariectomy on measures of mammary growth and development in prepubertal dairy heifers

Abstract: Previous studies in prepubertal heifers suggest that the magnitude of reduction in mammary parenchymal growth in response to ovariectomy varies with the age at which surgery is performed. We hypothesized that ovarian secretions are essential for initiating mammary development but not required to maintain allometric mammary growth in prepubertal dairy heifers. The objectives of this study were to determine the effect of staged ovariectomy during the prepubertal period on mammary growth and tissue composition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Samples of fixed parenchymal tissue were embedded in paraffin and tissue sections subsequently prepared, dewaxed, and stained with hematoxylin and eosin for general histology as described in previous studies (Velayudhan et al, 2012;Tucker et al, 2016).…”
Section: Histological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of fixed parenchymal tissue were embedded in paraffin and tissue sections subsequently prepared, dewaxed, and stained with hematoxylin and eosin for general histology as described in previous studies (Velayudhan et al, 2012;Tucker et al, 2016).…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Moreover, mammary tissue in prepubertal ruminants is sensitive to E 2 (Woodward et al, 1993;Ellis et al, 1998;Capuco et al, 2002). Despite the fact that circulating concentrations of E 2 are very low in prepubertal calves (Purup et al, 1993;Velayudhan et al, 2012Velayudhan et al, , 2015 when E 2 influence is removed from the calf via ovariectomy or the use of an E 2 receptor antagonist, mammary gland development is markedly reduced (Berry et al, 2003;Tucker et al, 2016). Perhaps enhanced early nutrition augments the action of mammogenic stimuli (such as E 2 ); for this reason, we selected E 2 to test our hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…One heifer was dropped from the study after harvest due to chronic illness. In a second experiment, Velayudhan et al [3], 20 Holstein heifer calves were randomly assigned to one of two treatments, ovariectomy (OVX; n = 8) or sham operation (INT; n = 12) (Figure 2). Surgeries were performed at 2, 3 and 4 months of age.…”
Section: Animals and Tissue Harvestingmentioning
confidence: 99%
“…No other genes were affected by age or interaction between treatment and age. uated the effect of exogenous GH (bST) (Huderson et al [2]) and ovariectomy (Velayudhan et al [3]) on mammary gland composition, proliferation and histology in prepubertal heifers. In contrast with work on older animals [25], we found that for these very young prepubertal heifers, exogenous GH had minimal impact on several measures of mammary development including: PAR mass, histological appearance and rate of cell proliferation (Huderson et al [1]).…”
Section: Effect Of Ovx On Transcript Abundancementioning
confidence: 99%
See 1 more Smart Citation